Regularized spectral log difference technique for ultrasonic attenuation imaging - Coila Pacompia, Andres Leonel (2017)
The attenuation coefficient slope (ACS) has the potential to be used for tissue characterization and as a diagnostic ultrasound tool, hence complementing B-mode images. The ACS can be valuable for estimation of other ultrasound parameters such as the backscatter coefficient. There is a well-known tradeoff between the precision of the estimated ACS values and the data block size used in spectral-based techniques such as the spectral log difference (SLD). This trade-off limits the practical usefulness of spectral-based attenuation imaging techniques. In this thesis work, the regularized spectral log difference (RSLD) technique is presented in detail and evaluated with simulations and experiments with physical phantoms, ex vivo and in vivo. The ACS values obtained when using the RSLD technique were compared to the ones obtained when using the SLD technique, as well as the ground truth ACS values obtained with insertion loss techniques.